Oral rehydration therapy of acute enteric infections - S. M. Zacharenko (Журнал инфектологии, 2014)
Analysis of holding rehydration therapy in acute intestinal infections in both civilian and military care facilities showed that the civilian centers of this type of therapy was appointed by 84,5% of patients, and in the military – 50,16%. The average duration of oral rehydration therapy was 4,0 days at the easy degree of weight, at middle – 5,3 and at a heavy flow – 5,7 days. On average, in easy degree of weight, patients received 1423.7 ml of liquid, at middle – 1092.6 ml at and a heavy flow - 1652.2 ml. Value for patients receiving only oral rehydration solution to patients who received only the infusion therapy and to receive both types of therapy was 1: 6,8: 2,4. Officinal drugs accounted for 62% of all appointments, often used Rehydron (47,7%) and ORS (16,5%).